Spastic paraplegia as the only symptom in two adult‐onset patients carrying a novel pathogenic variant in PYCR2. (17th October 2020) - Xie, J.‐J.; Ni, W.; Wei, Q.; Wu, Z.‐Y.
Abstract : A novel pathogenic PYCR2 variant and corresponding brain images in two patients characterized by spastic paraplegia.